Respuesta :

Answer:

What does the question ask you to do?

Step-by-step explanation:


Answer:

Vertex: -3, 0

y-intercept: 9

x-intercept: -3

Step-by-step explanation:

Convert into vertex form after factoring:

(x + 3)^2 + 0

Reorder your equation so it matches that of a parabola:

y = (x + 3)^2

Use the vertex form, y = a(x−h)^2 + k, to determine the values of a, h, and k.

a = 1

h = −3

k = 0

Now you have your vertex: (-3, 0)

To graph, use the intercepts.

To find the y-intercept, your x has to equal 0.

y = 0^2 + 6(0) + 9

y = 9

To find the x-intercept, your y has to equal 0.

x^2 + 6x + 9 = 0

Then use the quadratic formula to solve:

b ±  √b^2 - 4(a x c) /2a

Replace a with 1, b with 6 and c with 9:

-6 ±  √6^2 - 4(1 x 9) /2(1)

Solve:

-6 ±  √36 - 36 /2(1)

-6 + 0 /2

-6/2

x = -3

ACCESS MORE